Pemenuhan Kebutuhan Hidup Lansia Usia 72 Tahun Melalui Berjualan di Kawasan Aksara - Fitri Handayani; Najwatul Munawwarah; Flora Amelia; Nurlailiana; Sheltiva Fhazahra Dirda (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
This study aims to describe the fulfillment of elderly needs experienced by Mrs. Sri, an elderly woman who remains actively engaged in work as a fried snack vendor. This research employs a qualitative approach using direct interviews to obtain data related to physical condition, health, psychological, social, safety, and comfort aspects of daily life. The findings indicate that Mrs. Sri’s basic needs are generally fulfilled, particularly in terms of activity and social interaction, as reflected in her independence and continued productivity. However, several needs have not yet been optimally met, especially regarding health management, rest, and safety. Mrs. Sri experiences sleep disturbances, declining memory, and impaired vision in one eye, and has not undergone routine medical check-ups. Additionally, her fear of falling during daily activities highlights the need for a safer living environment and greater family support. Emotionally, Mrs. Sri carries psychological burdens influenced by aging and life experiences. In conclusion, although Mrs. Sri remains independent and active, comprehensive support is required to better fulfill elderly needs and improve her overall quality of life.